MICROBIAL DEGRADATION OF MAIZE COB AND ITS ASSESSMENT FOR USE AS BROILER FEED SUPPLEMENT (2012)
Maize, Zea mays is extensively cultivated in Nigeria with estimated total grain yield of 1.37 million tonnes per year. The maize by-product which includes the cob is readily available. This project was designed to convert maize cob to value-added products in broiler feed through microbial degradation using batch fermentation. One hundred and fifty kilogrammes of maize cob samples were collected from four dump sites in a farmers’ market in Oyo town. Bacteria and fungi were isolated using nutrient agar and potato dextrose agar media respectively. Identification of isolates was done by conventional methods and cellulase enzyme assay carried out by dinitrosalicylic acid method. The isolates with cellulase activities were then used for solid state fermentation. The process was then sealed up in fabricated tanks for bulk fermentation using Bacillus subtilis and Aspergillus niger solely. The derivatives labelled Bacteria Enriched Cob Product (BECP) and Fungi Enriched Cob Product (FECP) were subjected to chemical and microbiological analyses. The BECP and FECP were each substituted at 18%, 50% and 82% inclusions in compounded feeds while commercial feed served as control. These were fed to four-week old broiler chicken for six weeks in a completely randomized experimental set up of seven groups with ten chicks per group. Mean Weight Gain (MWG), Feed Conversion Ratio (FCR), economic performance, haematological indices and organ histopathology were determined. Data was analysed using inferential statistics at p = 0.05. Thirty-three (33) isolates made up of 19 bacteria and 14 fungi had cellulase activity. These were the genera Bacillus (10), Pseudomonas (8), Proteus (1) Aspergillus (6), Penicillium (4), Rhizopus (1), Mucor (1), Botryotrichum (1) and Geotrichum (1). The best cellulase producers were Aspergillus niger, 1.7 mg/ml and Bacillus subtilis 0.7 mg/ml with optimal activity at 40oC, pH 4.0 and 28oC, pH 7.0 respectively. Cellulose degradation ability of fungi 17.3% was higher than bacteria 6.6% while the crude protein levels were 7.5% and 9.5% respectively. The MWG (18.0g) of chicks fed BECP (82%), was much lower than the control (34.3g), FECP (18%), 38.9g; BECP (18%), 37.6g; FECP (50%) 31.0g and BECP (50%), 30.7g. The feed cost per kilogram gain for FECP (28%), N185.7; BECP (18%), N208.4 and FECP (50%) N227.4 were lower than the control N235.9. The FCR for BECP (82%), 8.4 was higher than the control value of 3.6. The red blood cell count for all treatments (1.7 – 2.6 x 106/mm3) did not differ significantly. However, white blood cell count was significantly higher in chicken fed with 82%, BECP (27.2 x 103/mm3) and 82% FECP, 20.4 x 103/mm3 compared to the other diets (11.2 – 16.2 x 103/mm3). Only the kidneys and lungs of chickens fed with 82% BECP were severely congested. Maize cob contained cellulolytic bacteria and fungi capable of degrading it at different extents. Substitution of either bacteria enriched product or fungi enriched product up to 50% were economically suiTable and safe for use as broiler chicken feed supplement.